2023
DOI: 10.1049/syb2.12071
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of circulating miRNAs and target mRNAs level in deep venous thrombosis patients

Abstract: Deep venous thrombosis is one of the most common peripheral vascular diseases that lead to major morbidity and mortality. The authors aimed to identify potential differentially expressed miRNAs and target mRNAs, which were helpful in understanding the potential molecule mechanism of deep venous thrombosis. The plasma samples of patients with deep venous thrombosis were obtained for the RNA sequencing. Differentially expressed miRNAs were identified, followed by miRNA‐mRNA target analysis. Enrichment analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…In APS, a major mechanism of hypercoagulability is mediated by aPL, which upregulate tissue factor on monocytes through the p38 MAPK and NF-κB pathways [ 43 ]. A previous study found that MAPK signaling pathway was associated with deep venous thrombosis [ 44 ]. However, the MAPK signaling pathway is a vast and complex network, with limited research on its association with venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In APS, a major mechanism of hypercoagulability is mediated by aPL, which upregulate tissue factor on monocytes through the p38 MAPK and NF-κB pathways [ 43 ]. A previous study found that MAPK signaling pathway was associated with deep venous thrombosis [ 44 ]. However, the MAPK signaling pathway is a vast and complex network, with limited research on its association with venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%